2018
DOI: 10.3390/ijms19020409
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Anti-Melanogenic Activities of Bamboo Stems (Phyllostachys nigra variety henosis) via PKA/CREB-Mediated MITF Downregulation in B16F10 Melanoma Cells

Abstract: Phyllostachys nigra var. henosis, a domestic bamboo species, has been attracting much attention; its bioactive compounds (especially in the leaf) show antioxidant, anti-inflammatory, and anti-obesity activities. Little information is available on the antioxidative and anti-melanogenetic activities of the bioactive compounds in bamboo stems. The anti-melanogenic and antioxidative activities of the EtOAc fraction (PN3) of a P. nigra stem extract were investigated in a cell-free system and in B16F10 melanoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 41 publications
4
50
0
2
Order By: Relevance
“…cAMP is a key second messenger in regulating skin pigmentation. Activation of PKA is known to induce CREB phosphorylation and stimulates MITF transcription [19]. Consistent with this previous finding, we observed that forskolin treatment markedly increased, while H89 inhibited, melanin production in B16F10 cells.…”
Section: Discussionsupporting
confidence: 91%
“…cAMP is a key second messenger in regulating skin pigmentation. Activation of PKA is known to induce CREB phosphorylation and stimulates MITF transcription [19]. Consistent with this previous finding, we observed that forskolin treatment markedly increased, while H89 inhibited, melanin production in B16F10 cells.…”
Section: Discussionsupporting
confidence: 91%
“…BP-4, a soluble UVB filter, can stabilise EGCG to produce effective anti-oxidants. Catechin preparations made with lipid ingredients are less stable in heat, so it is necessary to Gallego et al 2017, Spizzirri et al 2009, Nadim et al 2014, Feng et al 2014, Feng et al 2013, Zhong and Shahidi 2011, Muhammad et al 2014, Li and Seeram 2018, Choi et al 2018, Shoko et al 2018, Lima et al 2016 UV protection Improve the stability of catechins in sunlight and increase the UV protection effect Zhang et al 2016, Yoshino et al 2013, Niu et al 2017, Huang et al 2007, Martincigh and Ollengo 2016, Parisi et al 2012, Kim et al 2012, Xia et al 2005 Anti-microbial activities Demonstrates anti-microbial activity and develops pharmaceuticals and functional cosmetics de Oliveira et al 2017, Aoshima et al 2009, Goyal et al 2017 Anti-allergenic and antiinflammatory activities…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 106 phenolic compounds have been found using liquid chromatography assays coupled with electrospray ionisation for rapid profiling of phenolic compounds from red maple (Acer rubrum) leaves (Li and Seeram 2018). Bamboo stem extracts have demonstrated anti-melanogenic and anti-oxidative activities in a cell-free system and B16F10 melanoma cells (Choi et al 2018). The ethanol extract of the marula tree is very effective in boosting activities in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the scavenging activity of radicals or ROS is effective to suppress melanin production, and polyphenols with antioxidant activity may have excellent whitening effects [38]. Choi et al [39] showed that Korean bamboo stems (Phyllostachys nigra variety henosis) downregulated PKA/CREB-mediated MITF via scavenging of ABTS/DPPH radicals. And a 70% ethanolic extract of Nelumbo nucifera G. Leaf inhibited the expression of MITF, tyrosinase and TRPs with antioxidant activities such as electron donation ability and inhibition of xanthine oxidase [40].…”
Section: Discussionmentioning
confidence: 99%